Porous polymer-metal oxide negative electrode material, preparation method thereof and lithium ion battery

Through the solid phase couplet reaction to the in situ of metal oxides on the polygon aromatic hydrocarbon compound to form a porous polymer-metal oxide negative material, it solves the problem of insufficient performance and complicated preparation process of lithium-ion batteries. Lithium -ion battery negative materials with high ratio and magnification performance.

CN119361634APending Publication Date: 2025-01-24SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The low specific capacity and poor rate performance of the negative electrode material of the existing lithium-ion battery limit the overall performance of the battery, and the traditional methods of preparing carbon composite metal oxides have problems such as high cost, complex equipment and uneven material distribution.

Method used

The solid-phase coupling reaction method is used to perform heat treatment with metal chlorides on the basis of polycyclic aromatic hydrocarbon compounds to form porous polymer-metal oxide anode materials, allowing the metal oxide to grow in situ inside the porous polymer to enhance the material's Interaction and distribution uniformity of metal oxides.

Benefits of technology

It improves the specific capacity and rate performance of lithium-ion batteries, simplifies the preparation process, reduces costs, and achieves uniform distribution of metal oxides, making it suitable for large-scale production and commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361634A_ABST
    Figure CN119361634A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a porous polymer-metal oxide negative electrode material, a preparation method thereof and a lithium ion battery. The preparation method of the porous polymer-metal oxide negative electrode material provided by the invention comprises the following steps: carrying out heat treatment on mixed solid powder of a polycyclic aromatic hydrocarbon compound and a metal chloride for 5-8 hours to obtain the porous polymer-metal oxide negative electrode material. According to the preparation method disclosed by the invention, based on the solid-phase coupling reaction, the metal oxide is grown on the porous polymer in situ while the porous polymer is synthesized, so that the interaction between the metal oxide and the porous polymer is enhanced, and the particle size and distribution uniformity of the metal oxide can be effectively controlled; the distribution uniformity of the metal oxide in the prepared material is good, and extremely high specific capacity and rate capability are shown; the method is simple in steps and wide in raw material selection range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a porous polymer-metal oxide negative electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] In recent years, lithium-ion batteries have been widely used as energy storage and energy conversion devices, and have also shown extremely high value. The core components of lithium-ion batteries are composed of positive electrodes, negative electrodes, diaphragms and electrolytes. The capacity, energy density, life and other properties of lithium-ion batteries are closely related to the physical and chemical properties of the core materials. Since the first generation of commercial lithium-ion batteries using lithium cobalt oxide as the positive electrode material released by Sony in the last century, a variety of lithium battery positive electrode materials with different properties have been developed, such as lithium iron phosphate, ternary NCM, ternary NCA positive electrode materials, etc. These materials have higher advantages than lithium cobalt oxide in cost or performance, and have also made lithium-ion batteries more widely and deeply used in different application scenarios. Compared with the rapidly developing positive electrode materials, negative electrode materials also significantly affect the overall performance of the battery, but most commercial lithium batteries still use graphite as the negative electrode active material. The lower cost of graphite is one of the important reasons for its commercial popularity, but the lower specific capacity and poor rate performance of graphite have always limited the breakthrough in the performance of lithium batteries.

[0003] In order to develop negative electrode materials that can replace graphite to improve the performance upper limit of current lithium batteries, a lot of work has been done, and many negative electrode materials including carbon-based and non-carbon-based have been developed. Existing negative electrode materials can be divided into: insertion-type negative electrodes represented by lithium titanate, conversion-type negative electrodes represented by metal oxides, alloy-type negative electrodes represented by silicon, and lithium metal negative electrodes. Among them, lithium metal and silicon-based materials show large volume changes during lithium storage and de-lithiation, which cause damage to the intrinsic macrostructure and repeated destruction / regeneration of the surface solid-electrolyte film (SEI film) during the cycle process, ultimately causing battery failure and may even cause obvious safety problems. Although lithium titanate materials are stable, they have high chemical potentials and limited capacity, which reduces the overall energy density of the battery. Compared with carbon material negative electrodes, metal oxides show higher specific capacity while avoiding the safety issues caused by lithium metal. Therefore, they are considered to be a more feasible negative electrode material for lithium batteries.

[0004] In order to improve the electrochemical cycle stability of metal oxides, the preparation of carbon composite metal oxides is one of the most common and effective methods. However, there are often great difficulties in the preparation process of carbon composite metal oxides. The raw materials used in the traditional sol-gel method are expensive and take a long time, while the equipment cost of the hydrothermal method is high, the high temperature and high pressure process conditions are harsh, and the experimental cycle is long. These traditional methods cannot meet the production needs of large-scale preparation and future commercial materials. At the same time, carbon composite metal oxide materials prepared by traditional methods often have problems such as insufficient connection between the carbon base and the oxide base, and uneven distribution of metal oxides, which makes the material fail to achieve the expected performance.

[0005] In view of this, this invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a method for preparing a porous polymer-metal oxide negative electrode material, which has simple steps and is based on a solid-phase coupling reaction. On the basis of synthesizing a highly conductive porous polymer, a metal oxide is grown in situ to construct a polymer-metal oxide negative electrode material.

[0007] The second object of the present invention is to provide a porous polymer-metal oxide negative electrode material, which strengthens the interaction between the metal oxide and the porous polymer and has a uniform distribution of the metal oxide in the material.

[0008] A third object of the present invention is to provide a lithium ion battery having high specific capacity and rate performance.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides a method for preparing a porous polymer-metal oxide negative electrode material, comprising the following steps:

[0011] The mixed solid powder of the polycyclic aromatic hydrocarbon compound and the metal chloride is heat-treated for 5 to 8 hours to obtain the porous polymer-metal oxide negative electrode material.

[0012] Furthermore, the polycyclic aromatic hydrocarbon compound includes at least one of anthraquinone, pentacenequinone, tetraazapentacenequinone, perylene imide and polyimide.

[0013] Furthermore, the metal chloride includes at least one of aluminum chloride, ferric chloride, cobalt dichloride and cerium chloride.

[0014] Furthermore, the molar ratio of the metal chloride to the polycyclic aromatic hydrocarbon compound is ≥2.

[0015] Furthermore, the heat treatment includes: heating to 250-350° C. and heat preservation treatment in a protective atmosphere or vacuum environment.

[0016] Preferably, the heating rate of the heat treatment is 3 to 8 K / min.

[0017] Furthermore, after the heat treatment, a crude product is obtained; the crude product is washed with water until neutral, washed with a solvent and dried in sequence to obtain the porous polymer-metal oxide negative electrode material.

[0018] Furthermore, the washing with a solvent comprises: adding N,N-dimethylformamide, heating and stirring, and then washing with at least one of N,N-dimethylformamide, tetrahydrofuran, water and ethanol.

[0019] Furthermore, the drying includes: drying for more than 12 hours at a vacuum degree of less than 0.1 MPa and a temperature of 80 to 100°C.

[0020] In a second aspect, the present invention further provides a porous polymer-metal oxide negative electrode material, which is prepared by the method for preparing the porous polymer-metal oxide negative electrode material as described above.

[0021] In a third aspect, the present invention further provides a lithium-ion battery comprising the porous polymer-metal oxide negative electrode material as described above.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The preparation method of the porous polymer-metal oxide negative electrode material provided by the present invention is based on a solid phase coupling reaction. On the basis of synthesizing a highly conductive porous polymer, a metal oxide is in situ grown on the porous polymer. Metal oxide nanoparticles can be grown in the three-dimensional structural pores inside the polymer. On the one hand, the interaction between the metal oxide and the porous polymer is strengthened. On the other hand, the particle size and distribution uniformity of the metal oxide can be more effectively controlled, so that the metal oxide in the prepared material has a good distribution uniformity; thereby, the material exhibits extremely high specific capacity and rate performance.

[0024] 2. The preparation method of the porous polymer-metal oxide negative electrode material provided by the present invention has simple steps, mild reaction conditions, is suitable for a variety of polycyclic aromatic hydrocarbon compounds and metal chlorides, and can effectively regulate the structure and chemical composition of the product; metal halides that can serve as Lewis acids, as well as polycyclic aromatic hydrocarbon compounds of small molecule compounds or polymer compounds can be used as raw materials, which greatly expands the range of raw material selection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is the PXRD spectrum of pPQ-Fe2O3 prepared in Example 1 of the present invention.

[0027] Figure 2 This is the PXRD spectrum of pPQ-Al2O3 prepared in Example 2 of the present invention.

[0028] Figure 3 This is the rate performance of the battery assembled using the pPQ-Fe2O3 of Example 1 of the present invention.

[0029] Figure 4 The figure shows the rate performance of the battery assembled using the pPQ-Al2O3 of Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] The porous polymer-metal oxide negative electrode material and its preparation method and lithium ion battery of the present invention are described in detail below.

[0032] In some embodiments of the present invention, a method for preparing a porous polymer-metal oxide negative electrode material is provided, comprising the following steps:

[0033] The mixed solid powder of the polycyclic aromatic hydrocarbon compound and the metal chloride is heat-treated for 5 to 8 hours to obtain a porous polymer-metal oxide negative electrode material.

[0034] The present invention is based on a solid phase coupling reaction and uses a metal chloride as a strong Lewis acid catalyst. During the reaction, the metal chloride catalyzes the dehydrogenation of some carbon atoms in the polycyclic aromatic hydrocarbon compound, connects with the dehydrogenated carbon atom positions on adjacent molecules to form new carbon-carbon bonds, and realizes a polymerization reaction. At the same time, the oxygen-containing functional groups on the polycyclic aromatic hydrocarbon compound are opened and further detached to form metal oxides together with the metal ions in the metal chloride, and the metal oxides can be simultaneously formed in the process of forming the porous polymer.

[0035] The preparation method of the present invention, based on the synthesis of highly conductive porous polymers, in-situ grows metal oxide materials on the porous polymer materials, and can grow metal oxide nanoparticles in the three-dimensional structural pores inside the polymer. On the one hand, it strengthens the interaction between the metal oxide and the porous polymer, and on the other hand, it can also more effectively control the particle size and distribution uniformity of the metal oxide.

[0036] Compared with the metal oxide composite material synthesized by the existing method, the metal oxide particles grow on the surface of the substrate material, such as polymer or carbon material particles, the interaction between the metal oxide and the substrate material is small, and since there is no spatial volume constraint on the surface of the substrate material, larger particles may grow. In the preparation method of the present invention, the metal oxide mostly grows in the internal pores of the polymer and is tightly wrapped by the polymer, thereby improving the interaction between the metal oxide and the porous polymer, and the volume of the inner pore is limited, the size of the grown particles is restricted, and no larger particles will appear.

[0037] The preparation method of the present invention is suitable for various polycyclic aromatic hydrocarbon compounds and metal chlorides, and can effectively regulate the structure and chemical composition of the product.

[0038] In the existing preparation method, metal chloride and polymer precursor reduce the melting point by forming hydrogen bonds, realize mutual fusion, and finally form a transparent and clear precursor solution. This method greatly limits the types of metal chloride and polymer precursor. On the one hand, metal chloride is required as a good hydrogen bond acceptor. Metal chloride needs to have a special structure, such as tin chloride, etc., where the boiling point of tin tetrachloride is 115 ° C. It is very easy to boil and gasify during the reaction process, which will cause certain pollution to the entire reaction vessel, and bring great difficulties to large-scale production. On the other hand, due to the demand for hydrogen bonds in the mechanism, the precursor often uses a polymer material containing a large number of oxygen-containing functional groups, including ether bonds, carboxylic acid ester groups, etc., which also brings great restrictions on the scope of the precursor. The preparation method of the present invention can use metal halides that can be used as Lewis acids, and polycyclic aromatic hydrocarbon compounds can use both small molecule compounds and polymer compounds, which greatly expands the selection range and pairing quantity of polycyclic aromatic hydrocarbon compounds and metal chlorides of the reaction raw materials, and at the same time, the amount of the substance of the reaction raw materials each time is also significantly improved, which greatly improves the feasibility of large-scale production and special customized preparation.

[0039] In some embodiments of the present invention, the polycyclic aromatic hydrocarbon compound includes at least one of anthraquinone (AQ), pentacenequinone (PQ), tetraazapentacenequinone (TAPQ), perylene imide (PDI) and polyimide (PI).

[0040] In some embodiments of the present invention, the metal chloride includes at least one of aluminum chloride, ferric chloride, cobalt dichloride and cerium chloride; preferably, the metal chloride includes aluminum chloride and / or ferric chloride.

[0041] In some embodiments of the present invention, the molar ratio of the metal chloride to the polycyclic aromatic hydrocarbon compound is ≥2; for example, the molar ratio of the metal chloride to the polycyclic aromatic hydrocarbon compound can be 2, 3, 4, 5, 6, 7, and the like.

[0042] The present invention does not impose a strict limit on the molar ratio of the metal chloride to the polycyclic aromatic hydrocarbon compound, and can be adjusted according to actual needs and the size of the container.

[0043] In some embodiments of the present invention, the polycyclic aromatic hydrocarbon compound and the metal chloride are ground to obtain a mixed solid powder.

[0044] In some embodiments of the present invention, grinding includes using a mortar; the grinding can be performed in an air environment without requiring a special environment.

[0045] In some embodiments of the present invention, the heat treatment includes: heating to 250-350°C for insulation treatment in a protective atmosphere or a vacuum environment; typically but not limiting, for example, the heat treatment temperature can be 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or a range consisting of any two of them; the heat treatment time can be 5h, 6h, 7h, 8h or a range consisting of any two of them.

[0046] The present invention can generate a porous polymer-metal oxide negative electrode material by heat treatment at 250-350°C for 5-8h; if the temperature is higher and the time is longer, the metal oxide will be reduced by the polymer material to generate a metal element, which will not provide capacity as a metal oxide.

[0047] In some embodiments of the present invention, the heating rate of the heat treatment is 3 to 8 K / min; preferably, the heating rate of the heat treatment is 4 to 6 K / min; more preferably, it is 5 K / min.

[0048] In some embodiments of the present invention, the protective atmosphere includes, but is not limited to, argon or nitrogen.

[0049] In some embodiments of the present invention, the heat treatment comprises: placing a container containing the mixed solid powder in a tube furnace for heat treatment; preferably, the container includes but is not limited to a corundum boat or a corundum crucible.

[0050] The present invention uses a conventional heat treatment equipment tubular furnace to realize the reaction, which is more convenient and can adapt more reactants for each reaction.

[0051] In some embodiments of the present invention, after heat treatment, a crude product is obtained; the crude product is washed with water until neutral, washed with a solvent and dried in sequence to obtain a porous polymer-metal oxide negative electrode material.

[0052] In some embodiments of the present invention, washing with a solvent comprises: adding N,N-dimethylformamide, heating and stirring, and then washing with at least one of N,N-dimethylformamide, tetrahydrofuran, water and ethanol.

[0053] In some embodiments of the present invention, washing with a solvent comprises: adding N,N-dimethylformamide (DMF) and stirring at 110-130° C. for 4-15 hours, and then washing with N,N-dimethylformamide (DMF), tetrahydrofuran (THF), water and ethanol in sequence.

[0054] In some embodiments of the invention, the solvent does not include hydrochloric acid; hydrochloric acid would dissolve the metal oxide.

[0055] In some embodiments of the present invention, drying comprises: drying for more than 12 hours at a vacuum degree of less than 0.1 MPa and a temperature of 80 to 100° C.

[0056] In some embodiments of the present invention, a porous polymer-metal oxide negative electrode material is also provided, which is prepared by the above-mentioned method for preparing the porous polymer-metal oxide negative electrode material.

[0057] In the porous polymer-metal oxide negative electrode material prepared by the preparation method of the present invention, the interaction between the metal oxide and the porous polymer is strong, the metal oxide is distributed very evenly, and extremely high specific capacity and rate performance are exhibited.

[0058] In some embodiments of the present invention, a lithium-ion battery is provided, comprising the porous polymer-metal oxide negative electrode material.

[0059] Using the porous polymer-metal oxide negative electrode material of the present invention as the negative electrode material of a lithium ion battery is beneficial to improving the specific capacity and rate performance of the battery.

[0060] Example 1

[0061] The method for preparing the porous polymer-metal oxide negative electrode material provided in this embodiment comprises the following steps:

[0062] Pentacenequinone (3.08 g, 10 mmol) and ferric chloride (8.1 g, 50 mmol) were ground in a mortar to make the solid powders uniformly mixed, and then transferred to a corundum boat;

[0063] Put the corundum porcelain boat containing solid powder into a tube furnace, connect a small oil pump to the outlet of the tube furnace, evacuate until the pressure is below 0.1MPa, then introduce argon gas until the pressure in the tube reaches atmospheric pressure, repeat the above evacuation and ventilation operation three times to completely remove the air in the tube; set the tube furnace program to heat, raise the temperature to 350℃ at a rate of 5K / min and keep it for 5h to obtain a crude product, and then cool it down to room temperature naturally;

[0064] After the tube furnace is cooled to room temperature, the corundum porcelain boat is taken out, the crude product is added to DMF, heated to 120°C and stirred for 12 hours, then filtered while hot to obtain a filter cake; the filter cake is washed with DMF, THF, water and ethanol in sequence at room temperature, and then dried in a vacuum drying oven at 80°C under low pressure to obtain the product pPQ-Fe2O3.

[0065] Example 2

[0066] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 1, except that 50 mmol of ferric chloride is replaced by 50 mmol of aluminum chloride to obtain the product pPQ-Al2O3.

[0067] Example 3

[0068] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 1, except that 10 mmol of pentacenequinone is replaced by 10 mmol of anthraquinone to obtain the product pAQ-Fe2O3.

[0069] Example 4

[0070] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 3, except that 50 mmol of ferric chloride is replaced by 50 mmol of aluminum chloride to obtain the product pAQ-Al2O3.

[0071] Example 5

[0072] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 1, except that 10 mmol of pentacenequinone is replaced by 10 mmol of perylene diimide to obtain the product pPDI-Fe2O3.

[0073] Example 6

[0074] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 5, except that 50 mmol of ferric chloride is replaced by 50 mmol of aluminum chloride to obtain the product pPDI-Al2O3.

[0075] Example 7

[0076] The preparation method of the porous polymer-metal oxide negative electrode material provided in this embodiment refers to Example 1, except that 50 mmol of ferric chloride is replaced by 50 mmol of cobalt dichloride, the temperature is raised to 250° C. at a rate of 5 K / min and maintained for 5 h to obtain the product pAQ-CoO.

[0077] Comparative Example 1

[0078] The preparation method of the porous polymer-metal oxide negative electrode material provided in this comparative example refers to Example 1, with the only difference being that the crude product is added with hydrochloric acid and refluxed with stirring for 12 hours, then added to DMF, heated to 120°C and stirred for 12 hours, and then filtered while hot to obtain a filter cake; the filter cake is washed with DMF, THF, water and ethanol in sequence at room temperature, and then dried in a vacuum drying oven at 80°C under low pressure to obtain the product pPQ-Fe2O3.

[0079] Comparative Example 2

[0080] The preparation method of the porous polymer-metal oxide negative electrode material provided in this comparative example refers to Example 1, with the only difference being that the crude product is added with hydrochloric acid and refluxed with stirring for 12 hours, then added to DMF, heated to 120°C and stirred for 12 hours, and then filtered while hot to obtain a filter cake; the filter cake is washed with DMF, THF, water and ethanol in sequence at room temperature, and then dried in a vacuum drying oven at 80°C under low pressure to obtain the product pPQ-Al2O3.

[0081] Test example

[0082] The pPQ-Fe2O3 of Example 1 and the pPQ-Al2O3 of Example 2 were subjected to powder X-ray diffraction (PXRD) tests, and the results are as follows: Figure 1 and Figure 2 shown.

[0083] Figure 1 and Figure 2 In the X-ray spectrum, there are multiple lattice diffraction peaks and a large package peak in the range of 20° to 40°; Figure 1 The lattice diffraction peaks in the graphite basically match the positions of the PDF card standard XRD signals of α-Fe2O3. Figure 2 The lattice diffraction peaks in the sample basically match the positions of the PDF card standard XRD signals of Al2O3, indicating the presence of the corresponding metal oxides in the product, while the large package peaks correspond to the generated porous polymers.

[0084] The element distribution of pPQ-Fe2O3 of Example 1 and pPQ-Al2O3 of Example 2 was characterized by Mapping, and the results are shown in Table 1.

[0085] Table 1

[0086] C O Fe / Al Example 1 60.86% 23.42% 15.73% Example 2 72.12% 14.32% 13.56%

[0087] It can be seen from Table 1 that the Fe element in pPQ-Fe2O3 of Example 1 and the Al element in pPQ-Al2O3 of Example 2 both show uniform distribution, further illustrating that the metal oxide grows uniformly inside the porous polymer; the Mapping element content data also shows that a certain amount of metal oxide components are effectively compounded inside the porous polymer.

[0088] The porous polymer-metal oxide negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were respectively used to prepare electrode plates, and paired with lithium metal plates to assemble half-cells for electrochemical testing. The results are shown in Table 2.

[0089] The preparation method of the electrode plate comprises the following steps: a porous polymer-metal oxide negative electrode material, conductive carbon black and a binder are dispersed in N-methylpyrrolidone (NMP) in a mass ratio of 8:1:1, stirred at high speed to remove internal bubbles, and then coated on a copper foil by a scraper; then transferred to a blast oven and heated at 80°C to remove the NMP solvent, and then transferred to a vacuum drying oven and vacuum dried at 105°C overnight, and the dried electrode plate is taken out of the vacuum drying oven and cut into original sheets with a diameter of 14 mm as plates for battery assembly.

[0090] The above-mentioned electrode plates are used to assemble a half-cell with a lithium metal plate. The assembly method is as follows: the half-cell is assembled using a 2025-type button battery shell, which is placed in the following order: negative electrode shell, electrode plate, diaphragm, electrolyte, lithium sheet, gasket, spring sheet, positive electrode shell, and then pressurized to buckle the battery shell until it is tight. Among them, the electrolyte uses a commercially purchased lithium battery electrolyte, which is a 1 mol / L lithium hexafluorophosphate solution with a composition of ethylene carbonate: diethyl carbonate of 1:1 (volume ratio). The diaphragm uses a commercially purchased polypropylene diaphragm. The assembled battery is left to stand for 10 hours for electrochemical testing.

[0091] The battery was tested for electrochemical performance by a Xinwei electrochemical cycle tester. Three charge and discharge cycles were activated at a low current, and then the test was performed according to the set program. The data is recorded in Table 2. Among them, the battery assembled with the porous polymer-metal oxide negative electrode materials of Example 1 and Example 2 was subjected to multiple cycles of electrochemical testing at different rates. The rate performance is shown in Table 2. Figure 3 and Figure 4 shown.

[0092] Table 2

[0093]

[0094]

[0095] It can be seen from Table 1 that the lithium ion battery prepared using the porous polymer-metal oxide negative electrode material of the present invention exhibits high specific capacity and rate performance.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a porous polymer-metal oxide negative electrode material, characterized in that: The steps include: The mixed solid powder of the polycyclic aromatic hydrocarbon compound and the metal chloride is heat-treated for 5 to 8 hours to obtain the porous polymer-metal oxide negative electrode material.

2. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 1, characterized in that: The polycyclic aromatic hydrocarbon compound includes at least one of anthraquinone, pentacenequinone, tetraazapentacenequinone, perylene imide and polyimide.

3. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 1, characterized in that: The metal chloride includes at least one of aluminum chloride, ferric chloride, cobalt dichloride and cerium chloride.

4. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 1, characterized in that: The molar ratio of the metal chloride to the polycyclic aromatic hydrocarbon compound is ≥2.

5. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 1, characterized in that: The heat treatment comprises: heating to 250-350° C. and heat preservation treatment in a protective atmosphere or vacuum environment; Preferably, the heating rate of the heat treatment is 3 to 8 K / min.

6. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 1, characterized in that: After the heat treatment, a crude product is obtained; after the crude product is washed with water until neutral, washed with a solvent and dried in sequence, the porous polymer-metal oxide negative electrode material is obtained.

7. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 6, characterized in that: The washing with a solvent comprises: adding N,N-dimethylformamide, heating and stirring, and then washing with at least one of N,N-dimethylformamide, tetrahydrofuran, water and ethanol.

8. The method for preparing the porous polymer-metal oxide negative electrode material according to claim 6, characterized in that: The drying comprises: drying for more than 12 hours at a vacuum degree of less than 0.1 MPa and a temperature of 80 to 100°C.

9. A porous polymer-metal oxide negative electrode material, characterized in that: The porous polymer-metal oxide negative electrode material is prepared by the preparation method of any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The porous polymer-metal oxide negative electrode material comprises the porous polymer-metal oxide negative electrode material according to claim 9.